Legal Review Of The Position And Duties Of The Ethical Council In The Implementation Of Elections (Study on the Election Organizer Honorary Council) - Anggalana; Fathul Aziz (Cita konsultindo, 2025)
The principle of honesty and fairness is the principle of elections which is integrated with the principles of direct, general, free and secret elections after the reforms. The addition of the principle of honesty and fairness as one of the principles in the implementation of democratic elections is not without reason. The principle of